Proposal of a New Hybrid Breeding Method Based on Genotyping, Inter-Pollination, Phenotyping and Paternity Testing of Selected Elite F1 Hybrids - Rudolf-Pilih, Katarina; Petkovšek, Marko; Jakše, Jernej; Štajner, Nataša; Murovec, Jana; Bohanec, Borut (Frontiers in Plant Science, 2019)
We propose a novel method of F1 hybrid breeding that enables evaluation of large number of line to line crosses for their hybrid performance. Inbred lines (preferably doubled haploid - DH) are produced from heterozygous populations, genotyped and maintained. A group of lines is inter-pollinated randomly and their progeny examined. To identify elite F1 hybrids, these individual plants are selected by their superior phenotypic characteristics. Finally using paternity testing only of selected hybrids, the origin of paternal lines is revealed. To predict the number of F1 offspring needed in relation to the number of inbred lines being inter-pollinated, a mathematical formula was developed. For instance, using this formula for the inter-pollination of 60 distinct lines, the probability of obtaining all descendants of paternal-parent lines in a maternal-parent row represented at least once is achieved with 420 F1 plants in a row (p=0.95). In a practical experiment with white cabbage, DH lines were produced using microspore culture; plants were grown to maturity and genotyped at eight polymorphic SSR loci. Two groups of lines (36 and 33 lines per group) were inter-pollinated by two methods, either using cage pollination with bumblebees or using open pollination in isolated field. A total of 9,858 F1 plants were planted and based on their phenotypic characteristics 213 were selected as elite phenotypes. 99 of them were genetically diverse and 5 of them were selected as super elite. Selected plants were analysed by the same SSR markers and the paternal origin of selected F1 plants was determined. Out of 213 selected elite plants 48 were reciprocals thus exhibiting power of selection based on single plant. We clearly demonstrate that this new approach to hybrid development is efficient and we propose its use in various vegetable and crop species.